Іncomе- та іnside-туроперейтинги як інструменти управління регіональним розвитком туризму й гостинності (на прикладі запорізького регіону) - Сидорук, А. В.; Бортников, Є. Г.; Олексенко, Роман Іванович; Sydoruk, A.V.; Bortnykov, YE. H.; Oleksenko, Roman (Мелітополь : 2021, 2021)
UA: Розглянуто особливості регіонального розвитку туризму та гостинності, а також підприємств, які сприяють цьому процесу. Проаналізовано погляди вітчизняних і зарубіжних науковців щодо проблем розвитку туристичної галузі й індустрії гостинності в аспекті регіонального підходу. Виокремлено основні напрями роботи туроператорів на вітчизняному ринку туристичних послуг, а саме: outgoing, incoming та insiding; наведено їх характеристику. З метою аналізу іnside- та incoming- туроперейтингів у регіональному розвитку туризму й гостинності (на прикладі Запорізького регіону) визначено напрями стратегії для insidе-туроператорів щодо утримання ринкових позицій та отримання максимально можливого прибутку в умовах конкуренції на туристичному ринку. Теоретичні узагальнення проілюстровано докладним аналізом дорожньої карти «Колоритне Приазов’я», основною метою якої є розвиток туризму й індустрії гостинності Запорізького регіону на наступні десять років. Доведено, що на регіональний розвиток туризму та гостинності чинять вплив багато факторів, таких як територія регіону, транспортна мережа, інфраструктура, туристичні ресурси, номенклатура туристичних послуг, сезонність їх надання та ін. Саме ці фактори сприяють формуванню іnsidе- та incomе-турів для залучення туристів до регіону та країни загалом, тим самим підвищують її економічний розвиток. EN: Tourism in modern times has a significant impact on the economy of Ukraine in general and the economy of its regions in particular. At the regional level, the role of tourism is associated with the production of tourist services, the formation, sale and consumption of tourist products, ie with regional tour rating. The aim of the article is to analyze the inside and incoming tours in the regional development of tourism and hospitality. Research results. The impact of tourism and hospitality at the regional level is due to the growth of tourism product production, attracting personal savings of tourists, creating an active rational consumer market and increasing the investment attractiveness of the local tourism industry. The development of tourism and hospitality in the region is due to the attraction of savings of tourists, tourists, who with their own costs during the trip, provide the regional market with additional funds, thereby improving the economy of the region. Increasing the attractiveness of tourist resources and the level of quality of the regional tourist product, the formation of a positive image of the tourist region, make tourism infrastructure a very desirable object for investment. During the formation of tourist products in order to attract tourists to the region, it is necessary to analyze its external and internal factors, as well as social factors (availability of free time), demographic factors, political and legal, technical and technological factors, etc. All this is the object of regional tour rating. Focusing on the geography of touring, it is divided into outgoing, incoming and inside touring. In the framework of our study, the last two species were considered in more detail. Conclusions. The regional development of tourism and hospitality is influenced by many factors, such as: the territory of the region, transport network, infrastructure, tourist resources, the range of tourist services, the seasonality of their provision and others. It is these factors that contribute to the formation of inside- and income-tours to attract tourists to the region and the country as a whole, thereby increasing its economic development. Each tourist region has its own unique long history, formed structure, as well as natural, cultural, historical and socio-economic potential. The available opportunities can be considered a sufficient resource for the construction and successful implementation of the development strategy of the region and its individual micro-destinations.
Income- and inside-tour operations as tools of management of regional development of tourism and hospitality (on the example of zaporizhzya region)
Keywords: туризм; гостинність; регіональний розвиток; туристичний продукт; туроперейтинг; incoming; insiding; tourism; hospitality; regional development; tourist product; touring